Validation of the traditional Chinese version of the Sinus and Nasal Quality of Life Survey (SN-5) for children - Wan-Yu Lai; David J. Kay; Chang-Ching Wei; Fen-Wei Huang; Kai-Li Liang; Hung-Rong Yen (Pediatrics and Neonatology)
Background: Persistent sinonasal symptoms are common in children with chronic rhinosinusitis. The Sinus and Nasal Quality of Life (QoL) Survey (SN-5) was the first validated questionnaire measuring sinonasal-related QoL in populations aged 2–12 years. No norm has been established for Chinese-speaking countries. We translated the SN-5 into traditional Chinese and evaluated validity and reliability. Methods: From December 2016 to December 2017, healthy volunteers and children with persistent sinonasal symptoms were enrolled. Guardians of the participants completed the SN-5, a visual analog scale (VAS) of nasal symptoms, and the Obstructive Sleep Apnea-18 (OSA-18); the responses were used to assess internal consistency, discriminant validity, and treatment responsiveness. A nontreatment group was administered the SN-5 1 week later to assess test–retest reliability. Results: We recruited 31 healthy volunteers and 85 children with rhinosinusitis, 50 and 35 in the treatment and nontreatment groups, respectively. The SN-5 demonstrated good internal consistency (Cronbach's α = 0.86) and test–retest reliability (0.74, p < 0.01). It exhibited good discriminant validity between the healthy and rhinosinusitis groups (p < 0.001). The SN-5 scores were correlated with the VAS scores (0.63, p < 0.001). The effect size of the SN-5 scores was 0.51. The total SN-5 and OSA-18 scores changed significantly after 4-week treatment (p < 0.05) and demonstrated good responsiveness. The SN-5 and OSA-18 scores were significantly and positively correlated (r2 = 0.53, p < 0.001). Conclusion: Our traditional Chinese version of the SN-5 is reliable and valid for measuring sinonasal-related QoL in children in Chinese-speaking countries. Trial registration number: NCT04836403.